Analisis Pengaruh Lingkungan Sekolah dan Kinerja Guru terhadap Prestasi Belajar Siswa - Nusantara, Fajar Adipura; Noviansyah, Herli; Hermawan, Bambang (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Education serves as the primary foundation for human resource development. However, challenges such as passive learning continue to hinder the optimization of student learning outcomes. Two key external factors that significantly influence students’ academic experiences are the school environment and teacher performance. This study aims to analyze the impact of these two variables on students’ academic achievement. A quantitative research approach was employed, focusing on SMPIT under the Ibnu Rusydi Foundation in Cipondoh, Tangerang City. The study involved a census sample of 41 teachers. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression, including classical assumption tests, partial tests (t-test), and simultaneous tests (F-test). The results show that the school environment contributes 37.3%, and teacher performance contributes 59.4% to student achievement. These findings highlight the significant and complementary roles both factors play in shaping student success. The implication is that efforts to improve academic performance should prioritize creating a supportive school environment and enhancing teacher competence and effectiveness. Strengthening both elements can lead to more active learning engagement and better academic results.